2007
DOI: 10.1007/s11060-007-9505-1
|View full text |Cite
|
Sign up to set email alerts
|

Response of preclinical medulloblastoma models to combination therapy with 13-cis retinoic acid and suberoylanilide hydroxamic acid (SAHA)

Abstract: RA + SAHA additively induce BMP-2 transcription and medulloblastoma apoptosis. The combination may act through a p38 MAPK independent mechanism. Efficacy increased with cisplatin, which has implications for clinical trial design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…79 Subsequently, in vivo studies have demonstrated that a combination of RA with the histone deacetylase inhibitor suberoylanilide hydroxamic acid is effective in medulloblastoma xenografts as well as in transgenic mice. 80 Currently, RA is tested in clinical studies for children with medulloblastoma ( Table 2). …”
Section: Future Directions For Medulloblastoma/spnetmentioning
confidence: 99%
“…79 Subsequently, in vivo studies have demonstrated that a combination of RA with the histone deacetylase inhibitor suberoylanilide hydroxamic acid is effective in medulloblastoma xenografts as well as in transgenic mice. 80 Currently, RA is tested in clinical studies for children with medulloblastoma ( Table 2). …”
Section: Future Directions For Medulloblastoma/spnetmentioning
confidence: 99%
“…Synergistic anti-tumour activity between histone deacetylase inhibitors and retinoids has been observed in a variety of preclinical models [24,25] . A study suggested that the HDAC inhibitor LAQ824 has a greater antitumor activity in combination with 13-cis-retinoic acid in melanoma tumors [24] .…”
Section: Combination Therapies Improve the Anticancer Activities Of Rmentioning
confidence: 99%
“…A study suggested that the HDAC inhibitor LAQ824 has a greater antitumor activity in combination with 13-cis-retinoic acid in melanoma tumors [24] . Another study showed that the intracranial tumors in ND2:SmoA1 mice treated with retinoid acid + SAHA + cisplatin showed a 4-fold increase in apoptosis over controls, and a 2-fold increase over animals receiving only SAHA or retinoid acid + SAHA [25] . We and others have shown that retinoids combined with histone deacetylase inhibitors are synergistic [26,27] .…”
Section: Combination Therapies Improve the Anticancer Activities Of Rmentioning
confidence: 99%
“…RA has been shown in preclinical models to cause apoptotic cell death in medulloblastoma by promoting BMP-2 transcription (Hallahan et al, 2003). This results in production of soluble BMP-2 protein that induces p38 MAP kinase phosphorylation and ultimately apoptosis (Spiller et al, 2008). Recently a phase 3 trial has been opened to treat medulloblastoma with RA.…”
Section: Targeted Treatmentmentioning
confidence: 99%